Clinical aspects of paediatric mastocytosis: a review of 101 cases. (30th November 2011) - Lange, M.; Niedoszytko, M.; Renke, J.; Gleń, J.; Nedoszytko, B.
Abstract Background Cutaneous mastocytosis (CM) is a typical presentation of mastocytosis in children. However, systemic mastocytosis may also occur in children. Objective We tried to characterize the clinical features of childhood‐onset mastocytosis and estimate the value of the SCORMA (SCORing Mastocytosis) Index and serum tryptase levels as disease severity parameters. Methods In a survey of 101 children mastocytosis was diagnosed and classified according to World Health Organization criteria. In all the cases serum tryptase levels and the SCORMA Index were done to assess the extent and intensity of the disease. Results Cutaneous mastocytosis was diagnosed in 100 children; 84% of them presented maculopapular CM, 10% mastocytoma and 6% diffuse cutaneous mastocytosis. Moreover, systemic mastocytosis with bone marrow infiltration and associated with maculopapular CM was found in one case. There was a positive correlation of serum tryptase level to the SCORMA Index. Both the mean tryptase level and the mean SCORMA Index were elevated in diffuse cutaneous mastocytosis children when compared with other forms CM. A significantly higher mean tryptase level was found in children with flushing, hypotension, diarrhoea, extensive bullous lesions and osteoporosis or osteopenia. Conclusion Mastocytosis in children usually has a benign course. Nevertheless, severe mediator‐related symptoms and systemic involvement may appear. Therefore, a multidisciplinary approach involving careful monitoring of the serum tryptase level, SCORMA Index and the organ function is recommended. Both tryptase levels and the SCORMA Index are of a great value as disease severity parameters and they should be assessed simultaneously in all mastocytosis patients.